(untitled) (Research, Society and Development, 2022)
This article aims to address the numbering systems of pre-Columbian civilizations (Mayan, Inca and Aztec), based on an educational practice carried out in an elementary school class II of a school institution in the municipality of Vitória/ES. This practice was carried out in a sequence of activities, composed of four classes, in which we sought to (re)know some numbering systems of pre-Columbian civilizations, establishing their characteristics and their combination rules. For this, we used, as a didactic resource, elements of the History of Mathematics, which allowed discussions about the theme worked. We present the main characteristics to build a numbering system, according to authors such as Adair M. Nacarato. We chose as sources of investigation, texts that approach the history of the civilizations under study, considering their cultural context, to support the pedagogical procedures. At the end of the readings, discussions were held with the participants about the numbering systems, as well as the importance of knowing them. We found that some students understood the difficulty in building a numbering system as well as its logic, and that the chosen symbols would make writing difficult when using it in everyday situations or even in mathematical operations. In addition, we understand some of the contributions of the use of elements from the History of Mathematics in the teaching and learning process.